Mental toughness and burnout in junior athletes: A longitudinal investigation - Madigan, D. J.; Nicholls, A. R. (Psychology of Sport and Exercise, 2017)
Objectives: Mental toughness correlated negatively with burnout in several cross-sectional studies. It is unclear, however, whether mental toughness predicts changes in athlete burnout over time. Design: Two-wave longitudinal design. Method: We examined mental toughness and burnout in 93 junior athletes (mean age 17.7 years) across a three-month period of active training. Results: Regression analyses revealed that mental toughness predicted residual decreases in total burnout, reduced sense of accomplishment, physical and emotional exhaustion, and devaluation over time. Conclusion: As such, mental toughness may offer athletes protection from the experience of burnout symptoms in sport.